Production of Bitumen Modified with Low-Molecular Organic Compounds from Petroleum Residues. 7. Study of the Structure of Formaldehyde Modified Tars - Gunka, Volodymyr; Hrynchuk, Yurii; Demchuk, Yuriy; Donchenko, Myroslava; Prysiazhnyi, Yuriy; Reutskyy, Volodymyr; Astakhova, Olena (Видавництво Львівської політехніки, 2023)
Хімічним модифікуванням гудрону формальдегідом з використанням як каталізатора сульфатної кислоти отримано три зразки бітумного матеріалу з різними температурами розм’якшення 321, 332 і 356,4 К. Визначено груповий вуглеводневий склад сировини процесу модифікації (гудрону) та отриманих бітумів. Також здійснено FTIR-дослідження одержаних груп вуглеводнів (олив, смол та асфальтенів). Досліджено структурні перетворення та запропоновано можливий хімізм процесу модифікування гудрону формальдегідом.

Three samples of bituminous material with different softening temperatures of 321, 332, and 356.4 K were obtained by the method of chemical modification of tar with formaldehyde using sulfuric acid as a catalyst. The determination of the group hydrocarbon composition was carried out for the raw materials of the modification process (tar) and the resulting bitumens. An FTIR study of the obtained groups of hydrocarbons (oil, resins, and asphaltenes) was also carried out. The structural transfor¬mations were investigated and a possible chemistry of the tar modification process with formaldehyde was proposed.
Виробництво бітуму, модифікованого низькомолекулярними органічними сполуками із нафтових залишків. 7. Дослідження структури гудронів, модифікованих формальдегідом
Keywords: гудрон; бітум; формальдегід; хімічне модифікування; tar; bitumen; formaldehyde; chemical modification